1989
DOI: 10.1088/0031-9155/34/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Image reconstruction algorithm for single-photon-emission computed tomography with uniform attenuation

Abstract: A new method is presented for obtaining an analytical solution to the image-reconstruction problem in single-photon-emission computed tomography. The rigorous solution is introduced by applying an analytical continuation process to the two-dimensional Fourier transform of the image, which is derived from the one-dimensional Fourier transforms of projection functions. The calculations can be carried out in a short computation time without involving unstable procedures. Numerical simulations were made to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 7 publications
2
49
0
Order By: Relevance
“…Various reconstruction methods were developed under this assumption, see for example [5][6][7][8][9][10][11][12][13][14][15][16][17]. A nice theory unifying most of these methods in a common framework was presented in [18,19].…”
Section: Geometrically (E µ O P)(φ S) Just Like (A a P)(φ S)mentioning
confidence: 99%
“…Various reconstruction methods were developed under this assumption, see for example [5][6][7][8][9][10][11][12][13][14][15][16][17]. A nice theory unifying most of these methods in a common framework was presented in [18,19].…”
Section: Geometrically (E µ O P)(φ S) Just Like (A a P)(φ S)mentioning
confidence: 99%
“…This approach leads to a relationship between the circular harmonic decomposition of the Fourier transform of f and the circular harmonic decomposition of the Fourier transform of T µ f . An alternative method of inversion based on the circular harmonic decomposition of the Fourier transform of f and T µ f was derived by Tretiak et al [3] and Inouye et al [8] using two different approaches. In [5], Metz et.…”
Section: Introductionmentioning
confidence: 99%
“…suggested a weighted linear summation of positive and negative frequencies of the circular harmonic decomposition of the Fourier transform of projections for reconstruction. It was shown that different choices of weight functions provide reconstruction formulas proposed in [7,3,8].…”
Section: Introductionmentioning
confidence: 99%
“…The simple collimator routinely used in SPECT scans is the parallel-hole collimator. The image reconstruction algorithms with uniform attenuation correction for this parallel-beam geometry are well known (Bellini et al 1979, Tretiak and Metz 1980, Gullberg and Budinger 1981, Clough and Barrett 1983, Inouye et al 1989, Metz and Pan 1995 and an analytical image reconstruction algorithm with non-uniform attenuation correction for parallel-beam geometry was presented in Novikov (2002).…”
Section: Introductionmentioning
confidence: 99%